Dalīl al-Ākhirah inda Maulana Wahidudin Khan - Muhammad Shohibul Mujtaba; Raga Maulana Primadi (Tasfiyah: Jurnal Pemikiran Islam, 2021)
This article is written to review one of the new proving methods in the development of Kalam science, in order to face the modern-day materialism that is oriented towards all things physically as a dangerous threat to religion. This is because belief in religion, in addition to discussing physical things, also discusses the metaphysical matters. It includes faith in God and faith in the Hereafter, both of which are metaphysical. One of the new ideas that became an important theme in the study of contemporary Islamic scholars is the thought of Maulana Wahiduddin Khan. This article uses the type of Library research, with the study of the Kalam science approach. Subsequently, the researcher used a Descriptive method to describe the Akhirat proof according to Wahiduddin Khan. In proving the religious truth about life in the Hereafter, Khan combines kalam with evidence of strong experiments, explaining the importance of belief in the life of the Hereafter. And in combining Kalam with evidence of Experimentt, Wahiduddin Khan opened up the afterlife by describing some of the research that has been done by scientists in modern times which is based on the experiment by: 1) in terms of medical research, 2) terms of research psychology, 3) in terms of the study of the spiritual, With these three studies aimed at preventing human beings from adverse acts and in order to improve human morale to live better.